2020
DOI: 10.4081/cp.2020.1254
|View full text |Cite
|
Sign up to set email alerts
|

Acute Esophageal Necrosis: A Rare Case of Upper Gastrointestinal Bleeding from Diabetic Ketoacidosis

Abstract: Acute esophageal necrosis, also known as black esophagus or acute necrotizing esophagitis is a rare condition with roughly 154 cases reported in the literature. This condition is classically diagnosed on its endoscopic findings of a circumferentially black esophagus that abruptly ends at the gastroesophageal junction and transitions to normal gastric mucosa. When present, acute esophageal necrosis potentially signifies a poor prognosis with an overall mortality up to 36%. This case report describes a criticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Hyperglycemia in DKA leads to poor vascular flow and sustainable damage to the esophageal mucosal barrier [7,11]. Similarly, osmotic diuresis in DKA causes extreme volume depletion and hypoperfusion of the distal esophagus, resulting in ischemia and necrosis of the area [7,10,11]. Other associated comorbidities, end-stage renal disease in our case, can increase the risk and severity of AEN [2].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Hyperglycemia in DKA leads to poor vascular flow and sustainable damage to the esophageal mucosal barrier [7,11]. Similarly, osmotic diuresis in DKA causes extreme volume depletion and hypoperfusion of the distal esophagus, resulting in ischemia and necrosis of the area [7,10,11]. Other associated comorbidities, end-stage renal disease in our case, can increase the risk and severity of AEN [2].…”
Section: Discussionmentioning
confidence: 72%
“…Black esophagus has been reported in a few cases in association with diabetic ketoacidosis (DKA) [3][4][5][6][7][8][9][10]. In particular, a literature review showed a strong association between DKA and AEN in acute gastrointestinal bleeding [10]. The exact mechanism is not fully understood but few have been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between DKA and AEN has been described in the literature (14,(17)(18)(19)(20)(21)(22)(23). DKA has been reported to be one of the most common triggering events for AEN (3,4,9).…”
Section: Discussionmentioning
confidence: 92%
“…Wischnewsky gastric lesions and acute esophageal necrosis were also not identified in our case. The presence of hemorrhage in the gastric lumen is at least interesting, and we have the courage to say that if death would have occurred later, there would have been the possibility for the Wischnewsky spots to appear or even for acute esophageal necrosis to develop [12,13]. Many autopsies performed on DKA cases that have been reported in the literature speak about the absence of characteristic macro and microscopic changes [6,36].…”
Section: Discussionmentioning
confidence: 99%
“…There are authors who consider Armanni-Ebstein kidney injuries as pathognomonic for DKA [9,10]. Recent studies correlate Wischnewsky gastric lesions and acute esophageal necrosis with death caused by DKA [11][12][13].…”
Section: Introductionmentioning
confidence: 99%